Standardized Scale to Measure Attitude of Beneficiary Farmers towards Rastriya Krishi Vikash Yojana - Sunita Kumari and F. L. Sharma, (Indian Journal of Extension Education, 2017)
Due to non-availability of a proper scale for measuring the attitude of beneficiary farmers towards RKVY it wasthought necessary to construct a attitude scale for measuring the attitude of beneficiary farmers towards RKVY.Keeping this in view, an attempt has been made to develop a scale for measuring the attitude of beneficiary farmerstowards RKVY. Method of summated rating technique was used for construction of attitude scale for beneficiaryfarmers towards RKVY. Finely twenty six statements were selected from thirty eight statements for which “t” valueswere worked out.